Colton in the line of fire - Dees, Cindy (Harlequin romantic suspense, 2020)
"Dedicated forensic scientist Yvette Colton is hell-bent on solving a cold case double murder. So is overbearing detective Reese Carpenter. When Yvette's brutally attacked, Reese springs to her aid...and she notices that the lawman is as intoxicating as he is infuriating. Sparks between them ignite just as they try to outwit a desperate killer who wants to bring down the Colton dynasty--and especially Yvette."--